Pengabdian Masyarakat Pelatihan Pengelolaan Keuangan dan Bahasa Periklanan Digital untuk UMKM - Lalu Yayan Ardiansyah; palit, juliana; Pranasa, Risyaf Kudus; Miswaty, Titik Ceriyani; Sutarman; Lazuardi, Ashar Banyu (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The development of small and medium enterprises in Lombok is growing along with the development of industrial technology and tourism in Lombok. Based on data on the number of MSMEs in NTB, the City of Mataram ranks first with the most MSMEs in NTB with a total of 22,473 as of July 2021. However, in general, MSMEs in the city of Mataram still face obstacles such as capital, licensing, raw materials, product marketing, financial management and innovation. Based on observations made by the Community Service Team at Bumigora University, out of a total of 100 MSMEs surveyed, capital was the biggest obstacle for MSMEs in developing their business with a percentage of 37%, financial management 30%, promotion 17%, raw materials 15% , and others 11%. Based on the observational data, an action is needed to overcome the problems of MSMEs and help develop the businesses of MSME actors in the city of Mataram. The Bumigora University Community Service Team tries to facilitate MSMEs in facing challenges, especially those related to financial management and advertising by conducting training for MSME actors. MSME training is packaged in the form of seminars accompanied by practice in making digital financial reports and advertising language as a follow-up to this training.